Analysis of innovation networks financed by biotechnology and energy sector funds - Leonhardt Ribeiro, Wander; Silveira Porto, Geciane (Review of Business Management, 2015)
<!--[if gte mso 9]> <![endif]--> Objective – This paper assessed the formation of innovation networks by firms and institutions of science and technology (IST) so that they can receive financial resources from science and technology sector funds (SFs). SFs are the cornerstones of the Brazilian national system of innovation (NSI). As the funds were created slightly over a decade ago, it is high time they underwent revision. Design/methodology/approach – The research used data from projects offered by FINEP, RAIS and Economática. Beyond the pursuit of basic patents Derwent Knowledge of Reuters. Descriptive analyzes were performed, network analysis through Gephi software and applied a multiple regression to the available indicators on the impacts generated by FS. The indicators used originate from different areas of knowledge and are analyzed in light of the theory of open innovation. Findings – In the preliminary stage of the program, funds were largely allocated to the science and technology sector, but firms had a low level of participation in the projects. In addition, patent applications are below expectations at that stage, given that one of the aims of SF is the incentive for technological development. Practical implications – Despite the improved transparency in the Brazilian economy, restrictions on information do not permit the application of statistical tests to measure the impacts of investments in innovation Originality/value – The innovation networks were assessed by social network analysis, which indicated that most nodes (actors) are occupied by more active ISTs, lowering any expectations for a higher level of participation by firms. Some suggestions are made for improving incentive programs for innovation and their management.